VALUE ADDING OF BUFFALO MEAT IMPORTED FROM INDIA IN PROCESSED MEAT PRODUCTS - Babji, Abdul Salam; Ramaya, Komate (Proceeding Buffalo International Conference, 2013)
Malaysia imported more than 70% of its red meat from India in the form of frozen bone less buffalo meat. Ironically importers and consumers called this imported buffalo meat as "Indian Beef". Another 20 % meat import is mainly from Australia, Brazil & Argentina, while local beef production account for the 10%. The majority of red meat from India is widely utilized in local dishes and processed into hamburgers, sausages, meat balls and nuggets. Buffalo Meat from India is cheaper compared to local beef as well as Australian or other meat imports. About 35- 40 % of imported buffalo meat are further processed into value added meat products Â because of higher return as well as meeting demands for the fast food industry and Â convenience for the low income urban communities. Indian buffalo meat import is a big business dominated by more than a dozen of cold chain traders that monopolized the industry. Research & Development over the past 30 years has resulted in many papers published with seminars & proceedings on meat products developments and formulations, generating useful information to the local meat industry as well as government. Use of local palm fats and soy protein with buffalo meat has also resulted in improved processed meat products beneficial to the growing youth population who consumed a substantial amount of processed fast food meat based products.